REDEFINISI PERAN GURU DALAM PENDIDIKAN ISLAM: DARI PENGAJAR MENJADI PENDIDIK (MURABBI) - Ahmad Khoiriansyah; Izzah Nurul Aini; Heliza; Rifqi Khairul Anam (Makkah: Journal Of Islamic Studies, 2026)
The rapid development of science, technology, and globalization has significantly influenced the educational process, including Islamic education. In many educational institutions, teachers are often positioned merely as transmitters of knowledge, while the broader role of character building and moral development receives less attention. This study aims to examine the redefinition of teachers’ roles in Islamic education from being solely instructors to becoming educators (murabbi) who guide students comprehensively. This research employs a qualitative approach through library research by analyzing various scholarly literature related to Islamic educational philosophy and teacher professionalism. The findings reveal that the concept of murabbi emphasizes holistic development encompassing intellectual, spiritual, emotional, moral, and social dimensions. A murabbi is responsible not only for transferring knowledge but also for nurturing values, character, and religious commitment among learners. Therefore, the transformation of teachers into murabbi figures is essential to address contemporary educational challenges and to produce individuals who possess knowledge, faith, and noble character. The study concludes that strengthening the murabbi paradigm can improve the quality and relevance of Islamic education in modern society.